Glabridin inhibits osteosarcoma migration and invasion via blocking the p38‐ and JNK‐mediated CREB–AP1 complexes formation. Issue 4 (26th August 2018) - Jie, Zhiwei; Xie, Ziang; Zhao, Xiangde; Sun, Xuewu; Yu, Hejun; Pan, Xin; Shen, Shuying; Qin, An; Fang, Xiangqian; Fan, Shunwu
Abstract: Osteosarcoma is the most common bone malignancy, and it seriously affects the quality of life of affected children and adolescents. Glabridin (GLA), a major component of licorice root extract, has been reported to exert antitumor effects against a variety of tumor types; however, its effects on osteosarcoma have not been elucidated. In the current study, we investigate the effects and potential antimetastatic mechanisms of GLA on osteosarcoma in vitro and in vivo. Flow cytometry showed that GLA induced G2/M cell cycle phase arrest and promoted cell apoptosis. Transwell and wound‐healing assays showed that GLA significantly decreased the migration and invasion of osteosarcoma cells. Further western blotting and quantitative real‐time polymerase chain reaction showed that the expression of matrix metalloproteinase (MMP)‐2 and MMP‐9 in MG63 and HOS cells were reduced after GLA treatment. Moreover, western blotting demonstrated that GLA downregulated the phosphorylation of p38 mitogen‐activated protein kinases and c‐Jun N‐terminal kinase. A coimmunoprecipitation assay illustrated that formation of cAMP response element‐binding protein (CREB)–activating protein 1 (AP1) complexes and the DNA binding activities of CREB and AP1 in MG63 and HOS cells were impaired following treatment with GLA. Finally, GLA inhibited tumor growth and suppressed osteosarcoma cell metastasis in vivo. Overall, our findings highlight the potential of GLA as a therapeutic agent for the prevention and treatment of tumor metastasis. Abstract : Glabridin (GLA), a major component of licorice root extract, inhibits osteosarcoma metastasis through suppressing the activation of p38 and c‐Jun N‐terminal kinase (JNK) pathways to prevent cAMP response element‐binding protein (CREB)–activating protein 1 (AP1) complex formation and ultimately downregulate the transcription of matrix metalloproteinase (MMP)‐2 and MMP‐9, which are known to promote cancer cell invasion and migration.